Treatment Patterns and Clinical Outcomes of Chronic Urticaria: Two-year Follow-up Results from the Scandinavian AWARE Study - Simon F. Thomsen; Ellen C. Pritzier; Chris D. Anderson; Siri Juvik; Nicolas V. Baust; Rikke Dodge; Anna-Karin Dahlborn; Christian Vestergaard (Medical Journals Sweden, 2022)
The AWARE (A World-wide Antihistamine-Refractory chronic urticaria patient Evaluation) study investigated outcomes in patients with chronic urticaria refractory to H1-antihistamine. The objective of the current study was to analyse the effects of treatment on patients' symptoms and quality of life for a period of up to 2 years. Over the 2 years, there was clear improvement in the high rates of disease burden from baseline, as evidenced by lower scores for disease severity scales, better quality of life, and a decreasing rate of medical resource utilization. However, this is the result of treatment adherence to the guidelines in highly specialized Scandinavian urticaria centres, and has its basis in the relatively low treatment intensity and control at enrolment. There is a need for greater adherence to the treatment guidelines and better management of antihistamine-refractory chronic urticaria.